2017
DOI: 10.1002/2016jf004099
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Lateral Bedrock Erosion Rates Control Planation of Uplifting Folds in the Foreland of the Tian Shan, NW China

Abstract: Fluvial planation surfaces, such as straths, commonly serve as recorders of climatic and tectonic changes and are formed by the lateral erosion of rivers, a process that remains poorly understood. Here we present a study of kilometer‐wide, fluvially eroded, low‐relief surfaces on rapidly uplifting folds in the foreland of the southwestern Tian Shan. A combination of field work, digital elevation model analysis, and dating of fluvial deposits reveals that despite an arid climate and rapid average rock‐uplift ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 169 publications
(376 reference statements)
0
41
0
1
Order By: Relevance
“…Our data might indicate ongoing uplift along the South Tian Shan Thrust, but the Main Pamir Thrust, as well as the Tian Shan foreland north and east of the Atushi fold (including the Mutule fold), appear to be inactive (Figure 2). Modest earthquakes (M ≤ 5) that occurred between 2003 and 2010 and depths of 9-10 km ( Figure 2) are neither known nor expected to have produced surface displacements larger than the sensitivity of the InSAR (>4-10 cm over 7 years) [Bonilla, 1982;Biasi and Weldon, 2006]. Whereas slip rate variations during a seismic cycle could introduce uncertainties [Thatcher, 1984;Cattin and Avouac, 2000;Hilley et al, 2009], the observed uplift pattern is consistent with constraints on longer-term geologic uplift rates (Figure 3), as well as inferred basinward propagation of the deformation front over the past 25 Myr [Heermance et al, 2008;Chen et al, 2011;Thompson et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data might indicate ongoing uplift along the South Tian Shan Thrust, but the Main Pamir Thrust, as well as the Tian Shan foreland north and east of the Atushi fold (including the Mutule fold), appear to be inactive (Figure 2). Modest earthquakes (M ≤ 5) that occurred between 2003 and 2010 and depths of 9-10 km ( Figure 2) are neither known nor expected to have produced surface displacements larger than the sensitivity of the InSAR (>4-10 cm over 7 years) [Bonilla, 1982;Biasi and Weldon, 2006]. Whereas slip rate variations during a seismic cycle could introduce uncertainties [Thatcher, 1984;Cattin and Avouac, 2000;Hilley et al, 2009], the observed uplift pattern is consistent with constraints on longer-term geologic uplift rates (Figure 3), as well as inferred basinward propagation of the deformation front over the past 25 Myr [Heermance et al, 2008;Chen et al, 2011;Thompson et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
“…We compiled published initiation ages (0.4-1.6 Myr) and measured total structural relief (0.6-5.0 km) on published structural cross sections for the Mingyaole [Chen et al, 2005;Li et al, 2015], Kashi [Chen et al, 2007], Atushi [Scharer et al, 2004;Heermance et al, 2008], Mushi [Li et al, 2013;Thompson, 2013], and Mutule [Bufe et al, 2017] folds (Table S3 and Figure S8). As an exception, initiation of the Mutule fold was estimated from the published initiation age of the Atushi fold to the west [Chen et al, 2002;Scharer et al, 2004;Heermance et al, 2008] on the basis of interference between the two structures (Table S3).…”
Section: /2017gl073627mentioning
confidence: 99%
See 1 more Smart Citation
“…The T3 tread, as the most spatially extensive surface, can be traced ~4 km along the fold transect (Heermance et al, ). According to cosmogenic 10 Be depth profile dating, the T3 tread was abandoned 70–90 ka (Bufe et al, ). Despite the presence of terrace levels, the river channel creating them was not been preserved and perhaps was diverted to flow along the fold's northern flank and finally joins the Boguzi River (Figure a), in response to continuing uplift of the fold.…”
Section: The Atushi Anticline In the Kashi Fold Beltmentioning
confidence: 99%
“…Because the T3 tread does not span the entire fold width, this shortening represents a minimum shortening since the terrace abandonment. A combination with the terrace age of 70–90 ka (Bufe et al, ) yields a shortening rate of ≥0.3 mm/a. This rate appears to be much lower than the average Quaternary shortening rate of ~3.3 mm/a (Y. Chen et al, ).…”
Section: The Atushi Anticline In the Kashi Fold Beltmentioning
confidence: 99%